Tissue Repair in the Mouse Liver Following Acute Carbon Tetrachloride Depends on Injury‐Induced Wnt/β‐Catenin Signaling. Issue 6 (9th April 2019) - Zhao, Ludan; Jin, Yinhua; Donahue, Katie; Tsui, Margaret; Fish, Matt; Logan, Catriona Y.; Wang, Bruce; Nusse, Roel
Abstract : In the liver, Wnt/β‐catenin signaling is involved in regulating zonation and hepatocyte proliferation during homeostasis. We examined Wnt gene expression and signaling after injury, and we show by in situ hybridization that Wnts are activated by acute carbon tetrachloride (CCl4 ) toxicity. Following injury, peri‐injury hepatocytes become Wnt‐responsive, expressing the Wnt target gene axis inhibition protein 2 (Axin2). Lineage tracing of peri‐injury Axin2 + hepatocytes shows that during recovery the injured parenchyma becomes repopulated and repaired by Axin2 + descendants. Using single‐cell RNA sequencing, we show that endothelial cells are the major source of Wnts following acute CCl4 toxicity. Induced loss of β‐catenin in peri‐injury hepatocytes results in delayed repair and ultimately injury‐induced lethality, while loss of Wnt production from endothelial cells leads to a delay in the proliferative response after injury. Conclusion: Our findings highlight the importance of the Wnt/β‐catenin signaling pathway in restoring tissue integrity following acute liver toxicity and establish a role of endothelial cells as an important Wnt‐producing regulator of liver tissue repair following localized liver injury.